Brittle failure in the parallel-to-grain direction of multiple shear softwood timber connections with slotted-in steel plates and dowel-type fasteners. (20th August 2019) - Yurrita, Miguel; Cabrero, José Manuel; Quenneville, Pierre
Highlights: Brittle failure in multiple shear planes timber connections has been scarcely studied. An overview of the main existing models for brittle failure is given. A stiffness model is proposed to apply these models in the studied connections. A set of experimental tests is performed to assess the ability of the models. When the existing models are combined with the proposal, the accuracy is improved. Abstract: The multiple shear connection with slotted-in steel plates and dowel-type fasteners is a very efficient timber joint for large timber cross sections. It is used in practice, mainly due to its high capacity and its better performance under fire. However, when the number of inner plates is increased, instead of a ductile mechanism, brittle failure may govern its capacity. No standard deals explicitly with this kind of joint. A set of tests has been performed in order to study the brittle failure of this kind of connections. The test results are then compared with the available prediction models that study both ductile and brittle failure modes to assess their prediction accuracy. An improved model for the assessment of the brittle failure mode for the multiple shear connections with slotted-in steel plates and dowel-type fasteners is then proposed.